Perlindungan Hak Anak dalam Perkawinan Anak di Indonesia - Aisyah Salsabila Achmad; Laila Tuzzahro; Nor Heliza Febrianty; Widya Armade Oktavia (JOURNAL SAINS STUDENT RESEARCH, 2025)
Marriage in Islam is a sacred bond that not only unites two individuals physically but also serves as an act of worship and a moral responsibility to build a family founded on sakinah, mawaddah, and rahmah tranquility, affection, and compassion. In the Indonesian context, national law and Islamic law work hand in hand to regulate marriage through Law Number 1 of 1974, the Compilation of Islamic Law (KHI), and the amendment of Law Number 16 of 2019, which sets the minimum age of marriage at 19 years. This policy represents the state’s commitment to child protection as mandated by Law Number 35 of 2014 on Child Protection, aiming to prevent the negative impacts of early marriage that threaten children’s rights to life, education, and health. However, social realities still reveal challenges such as low legal awareness, cultural pressure, and economic factors. Therefore, synergy between the government, religious institutions, and society is essential to instill the understanding that law is not merely a formal regulation but a means of safeguarding humanity, ensuring that every marriage brings benefit and protects the future of the nation’s next generation.